2008
DOI: 10.1212/01.wnl.0000325057.33666.72
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia types 1, 2, 3, and 6

Abstract: Our study suggests that spinocerebellar ataxia (SCA) 1, SCA2, and SCA3 share a number of common biologic properties, whereas SCA6 is distinct in that its phenotype is more determined by age than by disease-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 21 publications
17
201
2
5
Order By: Relevance
“…Because approximately 25% of all patients with SCA6 are affected by such extracerebellar oculomotor signs, ICARS may be superior to SARA when correlating extracerebellar MR imaging findings with clinical dysfunction. 26 Closer inspection of the correlations between ICARS subscore groups and volumes of infratentorial structures revealed a significant correlation in SCA3 between cerebellar volume and oculomotor function, while in SCA6, brain stem volume correlated significantly to kinetic functions and oculomotor functions.…”
Section: Discussionmentioning
confidence: 93%
“…Because approximately 25% of all patients with SCA6 are affected by such extracerebellar oculomotor signs, ICARS may be superior to SARA when correlating extracerebellar MR imaging findings with clinical dysfunction. 26 Closer inspection of the correlations between ICARS subscore groups and volumes of infratentorial structures revealed a significant correlation in SCA3 between cerebellar volume and oculomotor function, while in SCA6, brain stem volume correlated significantly to kinetic functions and oculomotor functions.…”
Section: Discussionmentioning
confidence: 93%
“…A comprehensive study on the frequency of nonataxic symptoms was conducted in 2008 by Klockgether and colleagues who found that SCA6 had a lower frequency in all but one (rigidity) of the 16 nonataxic symptoms when compared to SCA1, 2 and 3. These features included a number of very common symptoms such as; brainstem oculomotor signs, hyperreflexia, extensor planter and muscular atrophy [159]. It was also found that disease severity is largely age-dependent rather than linked to expansion size.…”
Section: Sca6 Clinical Featuresmentioning
confidence: 96%
“…The CAG expansion is seen in the α 1A voltage-dependant calcium channel gene (CACNA1), localised to 19p13 [39]. The expansion in CACNA1 is located in the last exon of the gene (exon 47) and is relatively small compared to those in other SCA diseases, with a healthy range of 4-18 repeats and a disease range of 21-30 repeats, with most cases being reported as 22-23 repeats (Table 2) [159,160].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Brainstem oculomotor signs such as saccadic slowing or ophthalmoparesis are observed in 74% (Schmitz-Hübsch, et al, 2008). Reduction of saccade velocity can be detected in mildly affected patients and it is accentuated with the disease duration.…”
Section: Spinocerebellar Ataxia Type 1 (Sca1)mentioning
confidence: 99%